The lophogastrids (Crustacea: Peracarida: Lophogastrida) of Indonesia and its adjacent waters. An updated checklist - Yolanda, Rofiza; Lheknim, Vachira; B.a.r, Azman; Price, W. Wayne; Hendrickx, Michel E. (Zootaxa, 2023)
The zoogeographic distribution of lophogastrid species (Crustacea: Peracarida: Lophogastrida) occurring in the Indonesian waters is presented. For each species, data on general distribution, bathymetric ranges, habitat and localities reported on published data are provided. A total of 20 lophogastrid species belonging to three families and seven genera occur in Indonesian waters (about 38% of all known lophogastrids species worldwide), a number greater than other areas of Southeast Asia. Also, based on current information, the number of species or species richness is greater than other regions, such as Madagascar, North Pacific off Japan, Mediterranean, Canary Island, northern mid-Atlantic ridge, Iberian Peninsula, Mexico, and Angola Basin (SE Atlantic). Most of the Indonesian species are distributed worldwide, but one species, Lophogaster inermis appears to be endemic to Indonesia. Previous listings of Paralophogaster intermedius occurring in Southeast Asian waters is not verified in any collections, and has therefore been removed from our updated list.